2006
DOI: 10.1186/bf03352010
|View full text |Cite
|
Sign up to set email alerts
|

Inferred long term trends in lightning activity over Africa

Abstract: Global warming is becoming a reality, with growing evidence that anthropogenic activity on our planet is starting to influence our climate (IPCC, 2001). Due to the increase in significant weather-related disasters in recent years, it is important to investigate the role of global warming on such changes. In this paper we attempt to estimate the long term trends in lightning activity over tropical Africa during the past 50 years, using upper tropospheric water vapor as a proxy for regional lightning activity. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 20 publications
2
12
0
Order By: Relevance
“…This decreasing trend in thunderstorms is not peculiar to India. Worldwide, similar downward trends in the frequency of thunderstorms during the second half of the twentieth century have been reported for parts of the USA (Changnon and Changnon, ), parts of Russia and Kazakhstan (Gorbatenko and Dulzon, ), tropical Africa (Price and Asfur, ), Pakistan (Mir et al, ), China (Yu et al, ), the Baltic countries (Enno et al, ) and parts of Nigeria (Budnuka, ). The decreasing trend in the frequency of thunderstorm days over India could be a result of a reduction in atmospheric moisture, which itself is the result of a reduction in the frequency of monsoon depressions (Dash et al, ).…”
Section: Resultssupporting
confidence: 60%
“…This decreasing trend in thunderstorms is not peculiar to India. Worldwide, similar downward trends in the frequency of thunderstorms during the second half of the twentieth century have been reported for parts of the USA (Changnon and Changnon, ), parts of Russia and Kazakhstan (Gorbatenko and Dulzon, ), tropical Africa (Price and Asfur, ), Pakistan (Mir et al, ), China (Yu et al, ), the Baltic countries (Enno et al, ) and parts of Nigeria (Budnuka, ). The decreasing trend in the frequency of thunderstorm days over India could be a result of a reduction in atmospheric moisture, which itself is the result of a reduction in the frequency of monsoon depressions (Dash et al, ).…”
Section: Resultssupporting
confidence: 60%
“…The two periods (1970–1975 and 2002–2007) are in similar sections of the solar cycle (after sunspot maximum, with similar sunspot values); thus solar activity cannot explain the huge difference. We have no data for local (over southern Africa) lightning activity during the 1970–1975 period, but Price and Asfur [2006] found no significant changes over tropical Africa. Also note that Gy.…”
Section: Statistical Results For Midlatitude Stationsmentioning
confidence: 63%
“…The observed sharp decreasing trend of Thn is not specific to India. Similar decreasing trends in the frequency of Thn activity have been observed worldwide during the second half of the 20th century over parts of the United States (Changnon and Changnon, 2001), parts of Russia and Kazakhstan (Gorbatenko and Dulzon, 2001), tropical Africa (Price and Asfur, 2006), parts of China (Wei et al, 2011;Yu et al, 2016), the Baltic countries (Enno et al, 2014), Yola in northeast Nigeria (Budnuka, 2015), and Pakistan (Mir et al, 2006). Further, Yu et al (2016) found that a decreasing trend in the frequency of thunderstorms over China is due to a decrease in moisture transported over the region resulting from decreasing monsoonal rainfall.…”
Section: Methodsmentioning
confidence: 63%